The Effect of Integrated Education on the Knowledge of Hemodialysis Patients - Apriria EP; Reni Prima Gusty; Devia Putri Lenggogeni (GLOBAL HEALTH SCIENCE GROUP, 2024)
ESRD (End-Stage Renal Disease) patients receive inadequate information regarding fluid and dietary restrictions, and the current educational methods provided by nurses are not optimal and do not fully meet the needs of hemodialysis patients. This study aims to evaluate the effect of integrated education on the knowledge of hemodialysis patients at Raden Mattaher Public Hospital Jambi Method: The study is a quantitative research with a quasi-experimental design and a Pre-Test-Post-Test design. The sample size is 56, with 28 in the intervention group and 28 in the control group, using purposive sampling technique. The intervention group received integrated education for 4 weeks. The instrument used in this study measures knowledge using Curtin's knowledge The questionnaire met validity criteria with a Pearson correlation value > 0.40 and reliability with a Cronbach's alpha value > 0.70. The computerized data analysis results show a significant average difference in the intervention group's knowledge (p < 0.05). Based on this study, integrated education is effective in improving the knowledge of hemodialysis patients. The implementation of an integrated education program is recommended as the standard for educating hemodialysis patients.